EKONOMI PASTORAL: GAYA HIDUP KONSUMTIF DAN KEKERASAN DALAM RUMAH TANGGA - Salindeho, Veibe; Dendeng, Leonardo Caesar; Nani, Deissy; Palar, Dennis; Timomor, Jenifer Makarios; Wengen , Natalia Christine; Salindeho, Mila Enjeli; Manambe, Claudia Vain; Barangke, Rosita Karalina (HOSPITALITAS: Jurnal Pengabdian Kepada Masyarakat, 2024)
Abstract The study discussed the relationship between a consumer lifestyle and domestic violence. A consumptive life-style often involves excessive spending to satisfy personal wants without considering the needs or financial balance of the home. Studies show that financial pressures from a consumer lifestyle can be a factor that triggers or aggravates domestic violence. Factors such as financial tensions, unfulfilled feelings, and money-related conflicts can increase marital tension and cause violent incidents. The research methodology used is the research methodology of service learning research aimed at connecting education with the community and its needs.